Influence of Root Canal Posts on the Reattachment of Fragments to Endodontically Treated Fractured Incisors: An in vitro Experimental Comparison. Issue 2 (17th November 2015) - Mazzoleni, Sergio; Graf, Francesco; Salomon, Elena; Simionato, Francesco; Bacci, Christian; Stellini, Edoardo
Abstract: Objective: The aim of this study was to establish the benefits of inserting a fiberglass post when bonding tooth fragments after complicated coronal fractures. Methods: Thirty bovine incisors were randomly assigned to three groups: a control group of intact teeth (A), and two experimental groups (B and C). Coronal fragments were cut from the teeth in groups B and C, which then underwent root canal treatment, inserting posts in the teeth in group C. The coronal fragments were bonded to the teeth in both experimental groups using the same materials and technique, then the specimens were submitted to mechanical loading until fracture. Results: The specimens in the experimental groups had a lower resistance to mechanical loading than the intact teeth. The mean failure load was: 352.77 (SD ± 62.22) N in group A, 151.04 (SD ± 45.76) N in group B, and 168.61 (SD ± 33.59) N in group C. The difference between group A and the other two groups was statistically significant (analysis of variance test: p  < 0.0001), whereas there was no statistically significant difference in the force needed to fracture the teeth in groups B and C (Tukey's test: p  = 0.34). When the failure mode under loading was examined, the fractures in group C never involved new tooth substance beneath the adhesion interface, whereas in group B, this was only true in one in two cases. Conclusions: Inserting a post does not significantly improve the strength of restored teeth, but it may result in a more favorable fracture mode. Clinical Significance: Within the limitations of this in vitro study, reattaching the fragment of a fractured tooth does not seem to restore the tooth to its original load resistance. The findings of this study indicate that inserting a fiberglass post for reinforcement purposes in fractured teeth undergoing root canal treatment is unable to significantly improve their load‐bearing capacity by comparison with teeth repaired without inserting a post. However, the results of the present study suggest that inserting a post may result in a more favorable fracture mode in the event of further trauma.